Electrolyte-Dependent Sodium Ion Transport Behaviors in Hard Carbon Anode - Lee, Min Eui; Lee, Sang Moon; Choi, Jaewon; Jang, Dawon; Lee, Sungho; Jin, Hyoung-Joon; Yun, Young Soo (WILEY-V C H VERLAG GMBH, 2020)
A comprehensive study is conducted on hard carbon (HC) series samples by tuning the graphitic local microstructures systematically as an anode for SIBs in both carbonate- (CBE) and glyme-based electrolytes (GBE). The results reveal more detailed charge storage characters of HCs on the LVP section. 1) The LVP capacity is closely related to the prismatic surface area to the basal plane as well as the bulk density, regardless of electrolyte systems. 2) The glyme-sodium ion complex can facilitate sodium ion delivery into the internal closed pores of the HCs along with not well-ordered graphitic structures. 3) The glyme-mediated sodium ion-storage behavior causes significant decreases in both surface film resistance and charge transfer resistance, leading to enhanced rate capability. 4) The LVP originates from the formation of pseudo-metallic sodium nanoclusters, which are the same in a CBE and GBE. These results provide insight into the sodium ion-storage behaviors of HCs, particularly on the interrelationship between graphitic local microstructures and electrolyte systems. In addition, a high-performance HC anode with a plateau capacity of approximate to 300 mA h g(-1)is designed based on the information, and its workability is demonstrated in a full-cell SIB device.
Keywords: PLANE SURFACE-AREA; FUNCTIONAL-GROUPS; BASAL-PLANE; GRAPHITE; PERFORMANCE; STORAGE; INSIGHTS